An efficient isolation of foodborne pathogen using surface-modified porous sponge. (1st January 2019) - Choi, Yunho; Kim, Yong Tae; You, Jae Bem; Jo, Sung Hee; Lee, Seok Jae; Im, Sung Gap; Lee, Kyoung G.
Highlights: Functional and porous sponge is fabricated for isolation of pathogenic cells. Fabricated sponge exhibits high selectivity for water and oil absorption. Pathogenic bacteria can be successfully recovered from real food mixture. Fabricated sponge can be used as a platform for diagnosis of foodborne illness. Abstract: Rapid and efficient detection of pathogenic bacteria from food is critical to prevent epidemic food poisoning. However, the isolation of pathogenic bacteria from spoiled food is hampered by the lack of proper cell cultivation and/or isolation methods. Most of currently used methods suffer from complex, time-consuming culturing steps, low scalability, and high operation cost. Herein, we developed an alternative approach for the isolation of pathogenic bacteria directly from food using a surface-modified, highly porous sponge via initiated chemical vapor deposition (iCVD) process. A hydrophobic polymer, poly(2, 4, 6, 8-tetravinyl-2, 4, 6, 8-tetramethyl cyclotetra-siloxane) (pV4D4), was deposited conformally on amphiphilic 3-dimensional (3D) melamine sponge to incorporate hydrophobicity as well as oleophilicity to the porous sponge surface, which is appropriate for absorbing oil component selectively from food extracts. Furthermore, the surface-modified sponge was capable of the isolation of Escherichia coli O157:H7 ( E. coli O157:H7) from heterogeneous mixture with oil/water/food particles with undistinguisible efficiency compare to artificial model system. The surface-modified sponge developed in this study will be a novel platform for oil/water separation and isolation of foodborne pathogens directly from heterogeneous mixture to enhance the efficiency of molecular diagnostics.